2015
DOI: 10.18632/oncotarget.4203
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PI3K/Akt/mTOR signaling in the tumor stroma drives endocrine therapy-dependent breast tumor regression

Abstract: Improved efficacy of neoadjuvant endocrine-targeting therapies in luminal breast carcinomas could be achieved with optimal use of pathway targeting agents. In a mouse model of ductal breast carcinoma we identify a tumor regressive stromal reaction that is induced by neoadjuvant endocrine therapy. This reparative reaction is characterized by tumor neovascularization accompanied by infiltration of immune cells and carcinoma-associated fibroblasts that stain for phosphorylated ribosomal protein S6 (pS6), downstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…Mechanistically, MARCKS carries out the actin cytoskeleton arrangement function with its polybasic effector domain that cross-links actin filaments into bundles and sequesters bisphosphate (PIP2) [40], which is a component of phosphatidylinositol 3′-kinase (PI3K)/AKT pathways. Accordingly, it was recently reported that activation of the PI3K/Akt signaling cascade in the tumor stroma drives breast tumor regression [52], emphasizing the pivotal role of AKT in CAFs as in tumor cells. In addition, a key EMT transcriptional factor, Twist1, was shown to be responsible for MARCKS action on CAF characteristics, similar to that Twist1 induced the transformation of normal fibroblasts in gastric cancer [43].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, MARCKS carries out the actin cytoskeleton arrangement function with its polybasic effector domain that cross-links actin filaments into bundles and sequesters bisphosphate (PIP2) [40], which is a component of phosphatidylinositol 3′-kinase (PI3K)/AKT pathways. Accordingly, it was recently reported that activation of the PI3K/Akt signaling cascade in the tumor stroma drives breast tumor regression [52], emphasizing the pivotal role of AKT in CAFs as in tumor cells. In addition, a key EMT transcriptional factor, Twist1, was shown to be responsible for MARCKS action on CAF characteristics, similar to that Twist1 induced the transformation of normal fibroblasts in gastric cancer [43].…”
Section: Discussionmentioning
confidence: 99%
“…T47D human cell line requires a previous injection of 0,25 mg of 17β-estradiol to grow in NSG mice28.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of reports have suggested the importance of the PI3K/Akt/mTOR pathway through p70S6K- and 4EBP1-mediated translational regulation on cell proliferation and survival [35, 29]. The data demonstrated the activities on the Akt/mTOR signaling including the phosphorylation of Akt at both Thr308 and Ser473 residues in the activation loop and hydrophobic motif of the kinase, respectively, and phosphorylation of mTOR at Ser2448 that was dependent on the kinase activity (Figure 3B) [30, 31].…”
Section: Resultsmentioning
confidence: 99%
“…mTOR regulates various components involved in protein synthesis, in particular at G1 phase, including initiation and elongation factors, and biogenesis of ribosomes themselves [2933]. The data revealed that SPS-7 caused a profound inhibition of mTOR and related translational pathways, resulting in the down-regulation of cyclin D1 protein expression and G1 arrest of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%